Delineating African Catfish ( Clarias gariepinus Burchell, 1822) Populations Through Molecular Genetic Approaches to Contribute to Aquaculture Performance in Uganda - Tibihika, Papius Dias; Aruho, Cassius; Namulawa, Victoria; Ddungu, Richard; Atukunda, Gertrude; Aanyu, Margaret; Nkambo, Mujibu; Kwikiriza, Gerald; Vijayan, Thapasya; Curto, Manuel; Meimberg, Harald (Journal of applied ichthyology, 2025)
Aquaculture in Uganda is mainly anchored on two fish species: Nile tilapia ( Oreochromis niloticus ) and the Ugandan African catfish ( Clarias gariepinus ). The Ugandan C. gariepinus is popular among farmers nationwide because of its desirable traits, such as high growth rates, a broad array of trophic levels, and resistance to diseases and parasites. Nevertheless, the species’ productivity is limited by insufficient molecular genetic data that can be used to inform selective breeding efforts. We fill this gap by sequencing the mtDNA D‐loop of 192 C. gariepinus individuals from five major water bodies of Uganda. The results show that the Western Rift Valley lakes (Edward, George, and Albert) are more genetically diverse, with the least being the Central region lakes, particularly the Kyoga basin lakes. Fst values and the haplotype network group the C. gariepinus populations into two genetic clusters: the Western Rift Valley lakes (Albert, Edward, and George systems) and the Lakes Victoria and Kyoga systems. In particular, the current study reveals that Lakes Edward and George are likely a panmictic population. However, we noted genetic heterogeneity in L. Victoria, relatively indicating within‐lake genetic structure. These results present the initial steps for genetically characterizing the Ugandan C. gariepinus populations and are key to guiding the use of the wild stocks in aquaculture for selective breeding programs to propel fish farming in Uganda.